Mocking the just God? A theological critique of President Mnangagwa’s use of the name of God to justify his rule in Zimbabwe - Suspicion Mudzanire (AOSIS, 2021)
Zimbabwe’s President Emmerson Mnangagwa justified his unconstitutional ascendency to power after a military coup that dethroned former President Robert Mugabe in 2017 by claiming that ‘the voice of the people is the voice of God’. He repeated the claim in 2018 when Nelson Chamisa refused to recognise him as the legitimately elected president of the country after accusing him of rigging the 2018 elections. Mnangagwa’s use of God’s name to authenticate his rule raises the question: as one of the foundational attributes of God is justice, what does it mean for political leaders openly claiming to be ordained into office by him? This leads to a further question: Has Mnangagwa’s rule satisfied the demands that come with claiming to be ordained by God to rule, and what should be the church’s response towards Mnangagwa’s rule in view of God’s justice? This article uses God’s attribute of justice to critically evaluate Mnangagwa’s claim that ‘the voice of the people is the voice of God’. The claim is described and placed within Mnangagwa’s claims and insinuations to be a Christian. His current rule, which is characterised by violent repression and corruption is examined and evaluated. God’s attribute of justice is presented and highlighted in how it challenges Mnangagwa to reform his rule to align it with God’s nature of justice.